2019
DOI: 10.1177/1938640019863260
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Radiographic and Functional Outcomes After Tibiotalocalcaneal Arthrodesis With Bulk Femoral Head Allograft

Abstract: Background: Tibiotalocalcaneal (TTC) arthrodesis implementing adjunctive allografts is a method of limb salvage for patients with complex hindfoot osseous deficits, though outcome results are limited. The purposes of this study were to assess functional and radiographic outcomes after TTC arthrodesis with femoral head allograft and retrospectively identify prognostic factors. Methods: The authors reviewed 24 TTC arthrodesis procedures with bulk femoral head allografts performed by a single surgeon from 2004 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The same study also suggests that successful patient outcomes are possible without complete radiographic fusion. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The same study also suggests that successful patient outcomes are possible without complete radiographic fusion. 16 …”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature available regarding this technique, which reflects the difficulty in identifying suitable patients needing revision surgery with simultaneous subtalar degeneration and bone loss. Studies describing various techniques used to perform salvage TTC fusion generally involve small cohorts (between 10 and 25 patients) 8,16-19 ; therefore, it is difficult to draw conclusions about the success and complication rates of each technique. Only 3 studies have documented results of a similar salvage approach (21 patients overall), using the fibula as interposition graft.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative spacers include allograft (distal tibia 16 or femoral head 18,19 ); however, the risk of disease transmission (albeit low), cost, and donor availability are still concerns. 20,21 Transplanted bone may have a role as osteoconductive graft as compared with autologous bone, which is osteoconductive, osteogenic, and osteoinductive.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, union rates for foot/ankle arthrodesis with adjunctive LIPUS were found to be at least comparable to other therapies (Table 3). Others have reported lower union rates of 75% following IM nail use with allograft and additional adjunctive autograft [6]. Allograft has also been combined with demineralized bone matrix and iliac bone marrow aspirate during ankle and hindfoot arthrodesis with screw/plate [18].…”
Section: Diabetesmentioning
confidence: 99%
“…The incidence of non-union following foot and ankle arthrodesis can reach as high as 36% [4].To aid in healing and reduce revision risk, bone grafts and growth factors are used as adjuncts to foot/ankle arthrodesis [5]. Surgical foot/ankle arthrodesis augmented with autograft and/or allograft have yielded union rates as low as 75% [6]. Several recombinant human platelet-derived growth factor-enriched bone grafts have also been approved for use in foot and ankle applications [7], but the clinical outcomes have been mixed.…”
Section: Introductionmentioning
confidence: 99%